Predictive Capacity of Beat-to-Beat Blood Pressure Variability for Cardioautonomic and Vascular Dysfunction in Early Metabolic Challenge - Fares, Souha A.; Bakkar, Nour-Mounira Z.; El-Yazbi, Ahmed F. (Frontiers in Pharmacology, 2022)
Diabetic patients present with established cardiovascular disease at the onset of diagnostic metabolic symptoms. While premature autonomic and vascular deterioration, considered risk factors for major cardiovascular complications of diabetes, present in initial stages of metabolic impairment, their early detection remains a significant challenge impeding timely intervention. In the present study, we examine the utility of beat-to-beat blood pressure variability (BPV) parameters in capturing subtle changes in cardiac autonomic and vascular control distinguishing between various risk categories, independent of average BP. A rat model of mild hypercaloric (HC) intake was used to represent the insidious cardiovascular changes associated with early metabolic impairment. Invasive hemodynamics were used to collect beat-to-beat BP time series in rats of either sex with different durations of exposure to the HC diet. Linear (standard deviation and coefficient of variation) and non-linear (approximate entropy, ApEn, and self-correlation of detrended fluctuation analysis, ) BPV parameters were calculated to assess the impact of early metabolic impairment across sexes and feeding durations. HC-fed male, but not female, rats developed increased fat:lean ratio as well as hyperinsulinemia. Unlike linear parameters, multi-variate analysis showed that HC-fed rats possessed lower ApEn and higher , consistent with early changes in heart rate variability and blunting of parasympathetic baroreceptor sensitivity particularly in males. Moreover, logistic regression demonstrated the superiority of non-linear parameters of diastolic BPV in predicting a prediabetic disease state. Our findings support the use of non-linear beat-to-beat BPV for early detection of cardiovascular derangements in the initial stages of metabolic impairment.